ANALYSIS ON THE CONTROL FUNCTION OF THE DEWAN PERWAKILAN DAERAH (REGIONAL REPRESENTATIVES COUNCIL) THE REPUBLIC OF INDONESIA - Fatmawati, Fatmawati (UI Scholars Hub, 2012)
The Dewan Perwakilan Daerah (Regional Representatives Council - DPD) and the Dewan Perwakilan Rakyat (House of Representatives - DPR) are institutions which represent the people in the parliament of the Republic of Indonesia. However, these two institutions do not have equal powers, including the powers related to the control function. The DPD’s function related to control is provided for under Article 22D paragraph (3), Article 23E paragraph (2), andArticle 23F paragraph (1) ofthe ThirdAmendment to the 1945 Constitution of the Republic of Indonesia. The DPD can exercise control of the implementation of certain laws related to regional interests, the implementation of the State Budget, taxes, education and religion, reporting on the results of supervision exercised by it to the DPR; it receives the results of state finance audit conducted by the Badan Pemeriksa Keuangan (Audit Board - BPK), and provides its consideration to the DPR in electing members of BPK. Based on a comparison among various countries it is evident that although some countries have weaker control authorities compared to those of the DPD, it is the DPD elected directly through the general elections which has the weakest authority among them. Proportionate powers need to be granted to the DPD in order to ensure that that the objective of its establishment in representing the interests of the regions may be achieved.